2009
DOI: 10.1021/jp901397p
|View full text |Cite
|
Sign up to set email alerts
|

Axial Bonding in Alkylcobalamins: DFT Analysis of the Inverse Versus Normal Trans Influence

Abstract: Density functional theory has been applied to study the origin of the inverse and normal trans influence in alkylcobalamins. In order to cover the X-ray structural data available for alkylcobalamins with a variety of axial substituents, geometries of 28 related corrin-containing models have been optimized and analyzed. The BP86/6-31G(d) level of theory was applied which showed good reliability in reproducing the axial bond lengths. Comparison of experimental and calculated data allowed to conclude that the inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 67 publications
(132 reference statements)
5
38
1
Order By: Relevance
“…The Co-N ax bond to the N-donor of axial 5,6-dimethylbenzimidazole (dmbzm) is significantly longer in the 10-Br and 10-Cl derivatives (1.975 Å and 1.961 Å; 1.967 Å [1], respectively) than in [H 2 OCbl] + itself (1.925 Å [22]). Given the well-established trans influence in the cobalt corrins [45,46], this suggests that the Co-OH 2 bond is stronger in the 10-Br and 10-Cl derivatives than in [H 2 OCbl] + itself. The Co-N bond lengths to the corrin N-donors in the 10-Br and 10-Cl derivatives are somewhat longer than in H 2 OCbl + (Table S5 of the Supplementary material); the corrin cavity has expanded and the corrin fold angle (the angle between the mean planes defined by N21, C4, C5, C6, N22, C9, C-10 and C-10, C11, N23, C14, C15, C16, N24 [47]) is somewhat larger.…”
Section: The Spectroscopic Properties and Structure Of [Ho-(10-z)cbl] +mentioning
confidence: 90%
“…The Co-N ax bond to the N-donor of axial 5,6-dimethylbenzimidazole (dmbzm) is significantly longer in the 10-Br and 10-Cl derivatives (1.975 Å and 1.961 Å; 1.967 Å [1], respectively) than in [H 2 OCbl] + itself (1.925 Å [22]). Given the well-established trans influence in the cobalt corrins [45,46], this suggests that the Co-OH 2 bond is stronger in the 10-Br and 10-Cl derivatives than in [H 2 OCbl] + itself. The Co-N bond lengths to the corrin N-donors in the 10-Br and 10-Cl derivatives are somewhat longer than in H 2 OCbl + (Table S5 of the Supplementary material); the corrin cavity has expanded and the corrin fold angle (the angle between the mean planes defined by N21, C4, C5, C6, N22, C9, C-10 and C-10, C11, N23, C14, C15, C16, N24 [47]) is somewhat larger.…”
Section: The Spectroscopic Properties and Structure Of [Ho-(10-z)cbl] +mentioning
confidence: 90%
“…For example, a previous study by Burgi et al [18] on cobaloximes revealed that both axial distances lengthen when the electron donating ability of the X group increases. This behavior was called inverse trans influence, in contrast to the normal trans influence, which occurs when the lengthening of one axial bond corresponds to a shortening of the other [1][2][3][4][5][6][7][8]. On the basis of a careful reanalysis of the available data of the axial fragment, we provide here new evidence that both normal and inverse trans influences occur in cobaloximes.…”
Section: Introductionmentioning
confidence: 87%
“…The ability of a ligand to affect the metal-ligand bond of another ligand can be exerted electronically, by direct transmission through the metal (electronic influence), or sterically, by nonbonding interactions between the ligands (steric influence). The assignment of electronic or steric effects/influences allows rationalization of important properties of square planar [2,3] and octahedral [4][5][6][7][8] transition metal complexes, such as geometry, stability, and reactivity. Generally, the terms cis effect and trans effect refer to kinetics, whereas cis and trans influence refers to ground state and thermodynamic properties.…”
Section: Introductionmentioning
confidence: 99%
“…147,284 These differences have been previously explored by DFT methods, emphasizing the importance of inverse trans influence. 88,164 In the study presented in this chapter geometrical changes associated with electronically excited states of CNCbl were also investigated in order to explain distinct photophysical properties of CNCbl when compared to MeCbl.…”
Section: Discussionmentioning
confidence: 99%
“…Full geometry optimization was carried out employing the BP86/6-31G(d) (5d) level of theory, which has been found to be appropriate for structural analysis of cobalt corrinoids. 100,155,164 For each optimized geometry harmonic frequencies were calculated to verify that the optimized structure corresponds to a stable minimum. The geometry optimization and frequency calculations have been carried out using the Gaussian 03 suite of programs for the electronic structure calculations.…”
Section: Structural Modelsmentioning
confidence: 99%